Description of a new species of Imara Houlbert, 1918 (Lepidoptera: Castniidae) - Espinoza, Bernardo; González, Jorge M. (Zootaxa, 2005)
A new species of Imara Houlbert, 1918, is described from La Selva, Sarapiquí, Heredia Province, Costa Rica. Photographs of the male and female, and illustrations of the genitalia and wing venation are provided.